Human Cardiomyocyte Progenitor Cells in Co-culture with Rat Cardiomyocytes Form a Pro-arrhythmic Substrate: Evidence for Two Different Arrhythmogenic Mechanisms - Smit, Nicoline W.; Cócera Ortega, Lucia; Végh, Anna M. D.; Meijborg, Veronique M. F.; Smits, Anke M.; Klerk, Mischa; Tijsen, Anke J. M.; Tan, Hanno L.; Goumans, Marie-José H. T.; Boink, Gerard J. J.; Coronel, Ruben (Frontiers in Physiology, 2017)
Background: Cardiomyocyte progenitor cells (CMPCs) are a promising cell source for regenerative cell therapy to improve cardiac function after myocardial infarction. However, it is unknown whether undifferentiated CMPCs have arrhythmogenic risks. We investigate whether undifferentiated, regionally applied, human fetal CMPCs form a pro-arrhythmic substrate in co-culture with neonatal rat ventricular myocytes (NRVMs). Method: Unipolar extracellular electrograms, derived from micro-electrode arrays (8 × 8 electrodes) containing monolayers of NRVMs (control), or co-cultures of NRVMs and locally seeded CMPCs were used to determine conduction velocity and the incidence of tachy-arrhythmias. Micro-electrodes were used to record action potentials. Conditioned medium (Cme) of CMPCs was used to distinguish between coupling or paracrine effects. Results: Co-cultures demonstrated conduction slowing (5.6 ± 0.3 cm/s, n = 50) compared to control monolayers (13.4 ± 0.4 cm/s, n = 26) and monolayers subjected to Cme (13.7 ± 0.6 cm/s, n = 11, all p < 0.001). Furthermore, co-cultures had a more depolarized resting membrane than control monolayers (−47.3 ± 17.4 vs. −64.8 ± 7.7 mV, p < 0.001) and monolayers subjected to Cme (−64.4 ± 8.1 mV, p < 0.001). Upstroke velocity was significantly decreased in co-cultures and action potential duration was prolonged. The CMPC region was characterized by local ST-elevation in the recorded electrograms. The spontaneous rhythm was faster and tachy-arrhythmias occurred more often in co-cultured monolayers than in control monolayers (42.0 vs. 5.4%, p < 0.001). Conclusion: CMPCs form a pro-arrhythmic substrate when co-cultured with neonatal cardiomyocytes. Electrical coupling between both cell types leads to current flow between a, slowly conducting, depolarized and the normal region leading to local ST-elevations and the occurrence of tachy-arrhythmias originating from the non-depolarized zone.